Density and Temperature of the Upper Mesosphere and Lower Thermosphere of Mars Retrieved From the OI 557.7 nm Dayglow Measured by TGO/NOMAD. Issue 6 (3rd June 2022) - Aoki, S.; Gkouvelis, L.; Gérard, J.‐C.; Soret, L.; Hubert, B.; Lopez‐Valverde, M. A.; González‐Galindo, F.; Sagawa, H.; Thomas, I. R.; Ristic, B.; Willame, Y.; Depiesse, C.; et al.
Abstract: The upper mesosphere and lower thermosphere of Mars (70–150 km) is of high interest because it is a region affected by climatological/meteorological events in the lower atmosphere and external solar forcing. However, only a few measurements are available at this altitude range. OI 557.7 nm dayglow emission has been detected at these altitudes by the limb observations with Nadir and Occultation for Mars Discovery (NOMAD) aboard the ExoMars Trace Gas Orbiter (TGO). We develop an inversion method to retrieve density and temperature at these altitudes from the OI 557.7 nm dayglow limb profiles. We demonstrate that the atmospheric density around 90 and 140 km and temperature around 80 km during the daytime can be retrieved from the TGO/NOMAD limb measurements. The retrieved densities show a large seasonal variation both around 90 and 140 km and reach maximum values around perihelion period. This can be explained by temperature variation in the lower atmosphere driven by the dust content and Sun‐Mars distance. Temperature around 80 km is higher than predicted by general circulation models, which is tentatively consistent with the warm atmospheric layer recently discovered in nighttime. The temperature retrieval relies on the temperature dependence of the quenching coefficient of 1 S oxygen by CO2 . Further validation of this coefficient in the range of the Mars upper atmosphere is needed for the verification of the retrieved high temperature. Plain Language Summary: Density and thermal structures between 70 and 150 km of Mars atmosphere have not been extensively investigated because these altitudes are too low for in situ measurements by orbiters and too high for general remote‐sensing observations. Recently, a bright oxygen dayglow emission with green color (emitted at 557.7 nm) has been found in this altitude range. We combine a detailed photochemical model and widely used inversion scheme to develop a method to obtain density and temperature from the dayglow measurements. With this method, we successfully determine the density around 90 and 140 km, and temperature around 80 km. The densities show clear seasonal variations, with larger values during the southern spring‐summer season, stemming from the warmer lower atmosphere, a consequence of the shorter Sun‐Mars distance and heating by dust. Temperatures around 80 km are higher than the theoretical predictions. A similar warm atmospheric layer was found in nighttime by previous measurements, and our result suggests that it might also present in daytime. However, further experimental studies on temperature dependence of the related photochemical reactions are needed to firmly confirm the retrieved high temperatures. Key Points: We present that density around 90 and 140 km and temperature around 80 km of Mars atmosphere can be retrieved from OI 557.7 nm dayglow Density around 90 and 140 km increases around perihelion periods, which can be explained by temperature variation in the lower atmosphere Temperature around 80 km is higher than predicted by general circulation models